Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1007/s00542-010-1026-8
|View full text |Cite
|
Sign up to set email alerts
|

A FCOB packaged thermal wind sensor with compensation

Abstract: A two dimensional wind sensor was designed, fabricated and packaged on ceramic substrate instead of silicon substrate. The Ti/Pt heater and thermistors were fabricated using single lift-off process. The gold bumps were then sputtered and patterned on the chip using lift-off process again. Correspondingly, the Pb/Sn bumps were fabricated on the FR4 substrate using stencil printing method after metallization. The sensor chip was flip-chip packaged on the FR4 substrate, and the gap was filled with epoxy-based und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…Wind sensors have been created with thermoresistive technology [58]. Domí nguez et al created a wind sensor for use in Martian atmosphere on a space probe.…”
Section: Thermoresistivementioning
confidence: 99%
“…Wind sensors have been created with thermoresistive technology [58]. Domí nguez et al created a wind sensor for use in Martian atmosphere on a space probe.…”
Section: Thermoresistivementioning
confidence: 99%
“…While such a function has conventionally been carried out using macroscale devices, recent studies have demonstrated the feasibility of developing micro-electro-mechanical system (MEMS)based micro-flow sensors (Bora et al, 2018;Dagamseh et al, 2012;Ganji et al, 2017). Conventional acquisition methods for wind information include the heat flow sensor (Wu et al, 2011), hot-wire anemometer (Shen et al, 2010), ultrasonic wind sensor (Li et al, 2016) and piezoelectric hair flow sensor (Tao et al, 2016). In these papers, the minimum errors of heat flow sensor is 4% (velocity) and 2°(direction), the response time is 1s.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of thermoelectronic sensors, diodes, bi-polar junction transistors (BJT) and field effect transistors (FET) are commonly utilized for temperature sensing. 41 In recent years, numerous works on thermoresistive hot-wire [42][43][44] , hot-film [45][46][47] and calorimetric air flow sensors 17,48,49 have been reported in literature. Nevertheless, design and characterization of thermoresistive air flow sensors for high temperature applications (higher than 150°C) have been rarely reported.…”
Section: Introductionmentioning
confidence: 99%